A comparative study to evaluate the effect of limited access dressing (LAD) on burn wound healing. Issue 5 (17th February 2015) - Honnegowda, Thittamaranahalli M; Kumar, Pramod; Padmanabha Udupa, Echalasara G; Sharan, Anurag; Singh, Rekha; Prasad, Hemanth K; Rao, Pragna
Abstract: Biochemical and histopathological analyses are commonly used objective parameters in research and clinical fields to assess the healing status of burn wounds. In this study, the effect of newer intermittent negative‐pressure wound therapy in combination with moist environment [limited access dressing (LAD)] on burn wound healing is studied. Various biochemical parameters like hydroxyproline, hexosamine and total protein, and antioxidants like reduced glutathione (GSH), glutathione peroxidase (GPx) and oxidative biomarker malondialdhyde (MDA) were measured in the granulation tissue. Histopathologically, necrotic tissue, amount of inflammatory infiltrate, angiogenesis and extracellular matrix deposition (ECM) were studied to determine wound healing. A total of 55 patients were divided into two groups as follows: LAD group ( n = 28) and conventional dressing group ( n = 27). Patients treated with LAD have shown significant increase in the mean levels of (±SD) hydroxyproline (75·2 ± 26·30 versus 27·8 ± 15·5; P = 0·010), hexosamine (9·0 ± 1·99 versus 8·0 ± 1·18; P = 0·038), total protein (15·6 ± 8·23 versus 10·26 ± 4·94; P = 0·003), GSH (7·40 ± 1·91 versus 5·1 ± 1·28; P = 0·037), GPx (112·6 ± 46·4 versus 92 ± 32·4; P = 0·016), and decrease in MDA (6·5 ± 2·24 versus 1 0·6 ± 3·8; P = 0·002). Histopathologically, between LAD and conventional dressing groups, there was a significant difference after 10 days of treatment (mean±SE) in necrotic tissue of (LAD versus conventional dressing groups = 10 ± 1·8 versus 11·9 ± 2·6; P = 0·033), inflammatory cells (8·4 ± 1·9 versus 13 ± 3·46; P = 0·021), new blood vessels (12·5 ± 2·87 versus 9·4 ± 1·7; P = 0·047), ECM deposit (12·9 ± 2·41 versus 9·68 ± 1·3; P = 0·018) and showed comparatively fewer inflammatory cells, increased and well‐organised extracellular matrix deposit, more angiogenesis in LAD group as compared with that in conventional dressing group. To conclude, LAD exerts its beneficial effects on wound healing by reducing oxidative stress, decreasing necrotic tissue and amount of inflammatory infiltrate, and increasing ECM deposition and angiogenesis.